Comparison of Gleason score of Prostate Cancer at Ultrasound/MRI Fusion Target Biopsy vs. Systematic Transrectal Ultrasound Guided Biopsy with Final Gleason score at Radical Prostatectomy - Jinxing Yu; Ugo Falagario; Sarah G Winks; Kendal Angell; Ann S Fulcher; Mary A Turner; Sterling Jones; Rohan Kankaria; Steven C Smith (Archive of Urological Research - Peertechz Publications, 2022)
Purpose: To compare accuracy in predicting final Gleason Grade Group (GGG) of Prostate Cancer (PCa) of US/MRI fusion guided target (fBx) vs. systematic Transrectal Ultrasound-Guided (TRUS) biopsy, using histopathologic analysis at prostatectomy as the gold standard. Materials and methods: After obtaining IRB approval, we retrospectively reviewed records of patients who underwent Radical Prostatectomy (RP) from January 2014 through May 2019 with prior US/MRI fusion guided target or TRUS biopsy. The rates of upgrading (RP GGG > BX GGG), downgrading (RP GGG < BX GGG), and concordance (RP GGG = BX GGG) were compared between the fBx and TRUS groups. Age, PSA, PSA density, and prostate volume were also noted for all patients. Statistical analysis was utilized to assess the data. Results: A total of 348 men with complete clinical data were included in this study. The rate of downgrading and upgrading in the fBx group was less than in the TRUS biopsy group (14% vs. 19.6%, and 13.2% vs. 19.6%, respectively). The concordance rate was higher in the US-MR fBx group (72.9% vs. 60.7%, p < 0.05)) across all GGG. Notably, lower rates of concordance were found for GGG 1 (24.1%) and GGG 4 (3.6%) in the TRUS Bx group. Patients who underwent US-MR fBx had higher average PSA (9.4 vs. 6.5 ng/ml), higher PSA density (0.3 vs. 0.2 ng/ml2), and lower prostate volume (31 vs. 42 cc). Additionally, biopsy results showed a lower rate of GGG 1 (3.1% vs. 13.2%) and a higher rate of GGG 5 (14.7% vs. 5.5%) in the US-MR fBx group.  Conclusions: Target biopsy has a higher GGG concordance compared to TRUS biopsy (72.9% vs. 60.7%, p < 0.05). In addition, there was less downgrading or upgrading of final PCa GGG in the fBx groups compared to TRUS Bx (14% vs. 19.6%, 13.2% vs. 19.6%, respectively). This finding may have important implications for treatment decisions.